2020
DOI: 10.1101/2020.04.01.019299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis to design multi-epitope vaccines against Novel Coronavirus 19 (COVID19) infection, the ongoing pandemic emergency: an in silico approach

Abstract: 31The 2019 novel coronavirus (COVID19 / Wuhan coronavirus), officially named as 32Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), is a positive-33 sense single-stranded RNA coronavirus. SARS-CoV-2 causes the contagious 34 was not certified by peer review) measures against SARS-CoV-2 infection require the design and development of 37 specific and effective vaccine candidate. In the present study, we have screened 38 and shortlisted 38 CTL, 33 HTL and 12 B cell epitopes from the eleven Protein 39 s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 48 publications
(4 reference statements)
1
23
0
Order By: Relevance
“…At the same time, significant progress towards the isolation and design of vaccines (mRNA-1273 vaccine © 2020 Moderna, Inc) and neutralizing antibodies 9 has been made. A computational study identified the structural basis for multi-epitope vaccines 10,11 whereas in another study, the glycosylation patterns of the spike SARS-CoV-2 protein were computationally deduced 12 . In one study 13 , fully human single domain anti-SARS-CoV-2 antibodies with sub-nanomolar affinities were identified from a phage-displayed single-domain antibody library by grafting naïve CDRs into framework regions of an identified human germline IGHV allele using SARS-CoV-2 RBD and S1 protein as antigens.…”
Section: Mainmentioning
confidence: 99%
“…At the same time, significant progress towards the isolation and design of vaccines (mRNA-1273 vaccine © 2020 Moderna, Inc) and neutralizing antibodies 9 has been made. A computational study identified the structural basis for multi-epitope vaccines 10,11 whereas in another study, the glycosylation patterns of the spike SARS-CoV-2 protein were computationally deduced 12 . In one study 13 , fully human single domain anti-SARS-CoV-2 antibodies with sub-nanomolar affinities were identified from a phage-displayed single-domain antibody library by grafting naïve CDRs into framework regions of an identified human germline IGHV allele using SARS-CoV-2 RBD and S1 protein as antigens.…”
Section: Mainmentioning
confidence: 99%
“…The identified Ag-Patches were highly conserved in nature and were identified on the basis of significant number of overlapping epitope forming clusters (Figure 2, 3 & 4). Ag-Patches together, and to facilitate folding of the protein into its tertiary conformation (Hu et al, 2004;Wilson et al, 2013;Duits et al, 2003;Chen et al, 2013;Hajighahramani et al, 2017;Srivastava et al, 2019;Srivastava et al, 2018;Srivastava et al, 2020a;Srivastava et al, 2020b) ( Figure 1A, 1B, 2 (Table 3). from CTL-MPV-3); likewise, a total of IFN-γ inducing epitopes were screened from two HTL MPVs (83 from HTL-MPV-1 and 98 from HTL-MPV-2).…”
Section: Screening Of Potential Epitopes From Sars-cov-2 Proteomementioning
confidence: 99%
“…All the three CTL and two HTL MPVs were fitting into the ectodomain region of TLR3 receptor (Figure 7). T cell immune response driving long-term robust adaptive immunity in the vast majority of the population (Abdelmageed et al, 2020;Ahmed et al, 2020;Akhand et al, 2020;An et al, 2000;Banerjee et al, 2020;Baruah et al, 2020;Bhattacharya et al, 2020;Fast et al, 2020;Gragert et al, 2013;Gupta et al, 2020;Herst et al, 2020;Ismail et al, 2020;Khan et al, 2020;Lee et al, 2020;Liu et al, 2020;Lu et al, 2014;Mitra et al, 2020;Nerli et al, 2020;Poran et al, 2020;Ramaiah et al, 2020;Saha et al, 2020;Sheikhshahrokh et al, 2020;Singh et al, 2020;Srivastava et al, 2020a;Srivastava et al, 2020b;ul Qamar et al, 2020;Vashi et al, 2020;Yazdani et al, 2020). Numerous highly antigenic regions have also been reported from SARS-CoV-2 proteins which have been recognized on the basis of large population coverage by favorable binding with large number of HLA allele distributed amongst different ethnic human population worldwide (Grifoni et al, 2020b;Yarmarkovich and Warrington et al, 2020).…”
Section: Screening Of Potential Epitopes From Sars-cov-2 Proteomementioning
confidence: 99%
See 2 more Smart Citations